Novel implementation of laser ablation tomography as an alternative technique to assess grain quality and internal insect development in stored products. (March 2020) - Morrison, William R.; Lanba, Asheesh; Hall, Benjamin; Bruce, Alexander
Abstract: In the last century, there have been important advances in peering inside the internal grain environment. This has included electrical conductance mills, acoustical tools, near-infrared spectroscopy, and soft X-ray imaging. Each technique has their own advantages and limitations. In this current study, we describe a novel process for assessing grain quality and internal insect development in grain using laser ablation tomography (LATscan) and compare it to soft X-ray imaging for three life stages (larva, pupa, adult) of Sitophilus zeamais and Rhyzopertha dominica . Our results suggest that X-rays overestimated grain volume loss by about a quarter compared to LATscan. Moreover, LATscan produces a rich digital dataset on the level of microns that can be explored to ask biologically-relevant questions. We discuss the current limitations of LATscan in context with other techniques. Ultimately, the results highlight LATscan as a useful additional tool to further our understanding pest-commodity interactions in the postharvest supply chain. Highlights: Here, we evaluated the use of laser ablation tomography to determine grain quality. We found that laser ablation tomography was more accurate than soft X-rays. Use of this new technique may open up new research questions to explore.